A high-adhesion coating and preparation method thereof

By using a high-adhesion coating containing polyethylene glycol, sodium carboxymethylcellulose and other components on the lithium-ion battery separator, the existing membrane coating has solved the problem of poor water resistance and temperature resistance, and achieved the Better water and heat resistance.

CN119171009BActive Publication Date: 2025-02-14DEZHOU DONGHONG MEMBRANE TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411658661.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The coating of existing lithium-ion battery separators is poor in water and temperature resistance, which affects its normal use.

Method used

A high-adhesion coating is used, including polyethylene glycol, sodium carboxymethylcellulose, acrylate, glycidyl methacrylate, silicone rubber modified cellulose, modified maleimide and deionized water , prepared by stirring, a cross-net is formed to improve viscosity and heat resistance.

Benefits of technology

It significantly improves the water and heat resistance of the coating, enhances the adhesion with the battery pole sheet, and improves the surface wettability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of coatings, and discloses a high-adhesion coating and a preparation method thereof. The present invention adds polyethylene glycol, sodium carboxymethyl cellulose, acrylate, glycidyl methacrylate, silicone rubber modified cellulose, modified maleimide, and deionized water into a stirrer, stirs, and obtains a high-adhesion coating after the end. During the stirring process, the hydroxyl group in the silicone rubber modified cellulose and the amino group in the modified maleimide will form hydrogen bonds to form a cross-linked network, which increases its peeling force and viscosity on the diaphragm; the silicone rubber structure itself has good water resistance and heat resistance, and the maleimide group also has good heat resistance. The epoxy group in the epoxy cellulose and the carboxyl group in the intermediate 1 are subjected to a ring-opening reaction to introduce a hydroxyl group, thereby obtaining silicone rubber modified cellulose, which contains more grafting sites, introduces a large amount of silicone rubber, improves its degree of substitution, and further improves the heat resistance and water resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a high-adhesion coating and a preparation method thereof. Background Art

[0002] The diaphragm is one of the important components of the battery, which plays the role of isolating the positive and negative electrodes and providing ion channels. The diaphragm is generally made of PE, PP or PE / PP composite film, and an alumina ceramic coating is set on its surface to improve the heat resistance of the battery diaphragm. The structure of the lithium-ion battery diaphragm currently used is: a ceramic coating is coated on one side of the substrate, and an organic polymer electrolyte coating is coated on both sides. However, the coating has poor water resistance and temperature resistance, which will affect its normal use. Therefore, how to avoid this phenomenon is the key to solving the problem. For example, patent CN112909426A discloses a lithium battery modified coating diaphragm and its preparation method. The invention does not increase the amount of PVDF material and improves the adhesion between the diaphragm coating and the battery pole piece, and improves the surface wettability of the material, but its water resistance and heat resistance are not improved. Summary of the invention

[0003] In view of the deficiencies of the prior art, the present invention provides a high-adhesion coating and a preparation method thereof, which has good water resistance and heat resistance.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high adhesion coating, comprising the following components by weight: 1-2 parts by weight of polyethylene glycol, 0.8-1.1 parts by weight of sodium carboxymethyl cellulose, 5-8 parts by weight of acrylate, 6-9 parts by weight of glycidyl methacrylate, 4-8 parts by weight of silicone rubber modified cellulose, 7-10 parts by weight of modified maleimide, and 10-15 parts by weight of deionized water.

[0005] Preferably, the preparation method of the silicone rubber modified cellulose is:

[0006] (1) Adding the polymerization inhibitor butylated hydroxytoluene, the catalyst chloroplatinic acid and acrylamide to N,N-dimethylformamide solvent, stirring evenly, then adding silicone rubber, ultrasonically dispersing evenly, reacting at 65-80°C for 6-14h, cooling after reaction, centrifuging, washing and drying to obtain amino silicone rubber;

[0007] (2) Add maleic anhydride and pimaric acid into the reactor, heat in an oil bath at 110-120°C for 18-22 minutes, then add amino silicone rubber under stirring, continue to react for 3-6 hours after addition, cool to room temperature after completion, wash, and obtain intermediate 1;

[0008] (3) Add 5-10 parts by weight of cellulose to a sodium hydroxide aqueous solution, then dropwise add 9-14 parts by weight of epichlorohydrin and ethanol solvent, and stir to react at 65-80° C. for 3-6 hours to obtain epoxy cellulose, then continue to add 8-13 parts by weight of intermediate 1 and 0.1-0.3 parts by weight of triethylamine catalyst to carry out a ring-opening reaction, react at 70-95° C. for 6-10 hours, filter and wash after the reaction to obtain silicone rubber modified cellulose.

[0009] In the above reaction process, the alkenyl group in acrylamide and the silicon-hydrogen bond in the silicone rubber undergo addition reaction to introduce the amino group, thereby obtaining the amino silicone rubber; the anhydride group in maleic anhydride pimaric acid and the amino group in the amino silicone rubber undergo amidation reaction to introduce the carboxyl group, thereby obtaining the intermediate 1; the epoxy group in epoxy cellulose and the carboxyl group in the intermediate 1 undergo ring-opening reaction to introduce the hydroxyl group, thereby obtaining the silicone rubber modified cellulose.

[0010] Preferably, the mass ratio of the polymerization inhibitor butylated hydroxytoluene, the catalyst chloroplatinic acid, acrylamide and the silicone rubber in (1) is 0.01-0.02:0.02-0.03:1:1.1-1.2.

[0011] Preferably, the mass ratio of maleic anhydride pimaric acid to amino silicone rubber in (2) is 1:1.1-1.6.

[0012] Preferably, the mass fraction of the sodium hydroxide aqueous solution in (3) is 2-4%.

[0013] Preferably, the modified maleimide is:

[0014] S1. Add 4-maleimidophenol and intermediate 1 to N,N-dimethylformamide solvent, stir evenly, continue to add p-toluenesulfonic acid catalyst, react at 85-110°C for 6-10h, and then distill under reduced pressure and wash to obtain intermediate 2;

[0015] S2. Add 7-10 parts by weight of intermediate 2 and 6-15 parts by weight of mercaptoethylamine to 1,4-dioxane solvent, stir to dissolve, then add 0.1-0.4 parts by weight of triethylamine catalyst, react at 55-70° C. for 8-12 hours, filter and wash after reaction to obtain modified maleimide.

[0016] In the above reaction process, the phenolic hydroxyl group in 4-maleimidophenol and the carboxyl group in intermediate 1 are subjected to esterification reaction to introduce an olefin group, thereby obtaining intermediate 2; the olefin group in intermediate 2 and the thiol group in mercaptoethylamine are reacted to introduce an amino group, thereby obtaining modified maleimide.

[0017] Preferably, the mass ratio of 4-maleimidophenol, intermediate 1, and p-toluenesulfonic acid catalyst in S1 is 1:1.1-1.2:0.01-0.03.

[0018] Preferably, the preparation method of the high adhesion coating is: adding polyethylene glycol, sodium carboxymethyl cellulose, acrylate, glycidyl methacrylate, silicone rubber modified cellulose, modified maleimide, and deionized water into a stirrer, stirring at 25-30° C. for 5-10 minutes, and obtaining a high adhesion coating after the stirring.

[0019] The invention adds polyethylene glycol, sodium carboxymethyl cellulose, acrylate, glycidyl methacrylate, silicone rubber modified cellulose, modified maleimide and deionized water into a stirrer, and stirs to obtain a high-adhesive coating.

[0020] During the stirring process, the hydroxyl groups in the silicone rubber-modified cellulose and the amino groups in the modified maleimide will form hydrogen bonds to form a cross-linked network, which increases its peeling force and viscosity on the diaphragm; the silicone rubber structure itself has good water resistance and heat resistance, and the maleimide group also has good heat resistance. The epoxy group in the epoxy cellulose and the carboxyl group in the intermediate 1 are subjected to a ring-opening reaction to introduce hydroxyl groups, thereby obtaining silicone rubber-modified cellulose. Cellulose contains more grafting sites, and the introduction of a large amount of silicone rubber increases its degree of substitution, further improving the heat resistance and water resistance of the coating. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] (1) Add 0.01 g of inhibitor dibutyl hydroxytoluene, 0.02 g of catalyst chloroplatinic acid, and 1 g of acrylamide to 60 ml of N,N-dimethylformamide solvent, stir evenly, then add 1.1 g of silicone rubber, disperse evenly by ultrasonication, react at 65 ° C for 6 h, cool after reaction, centrifuge, wash and dry to obtain amino silicone rubber;

[0024] (2) 1 g of maleic anhydride pimaric acid was added to the reactor, heated in an oil bath at 110°C for 18 min, and then 1.1 g of amino silicone rubber was added under stirring. After the addition, the reaction was continued for 3 h. After the reaction was completed, the reaction was cooled to room temperature and washed to obtain intermediate 1.

[0025] (3) Add 5 g of cellulose to a 2% sodium hydroxide aqueous solution, then dropwise add 9 g of epichlorohydrin and 75 ml of ethanol solvent, stir and react at 65 °C for 3 h to obtain epoxy cellulose, then add 8 g of intermediate 1 and 0.1 g of triethylamine catalyst to carry out a ring-opening reaction, react at 70 °C for 6 h, filter and wash after the reaction to obtain silicone rubber modified cellulose;

[0026] (4) Add 1 g of 4-maleimidophenol and 1.1 g of intermediate 1 to 55 ml of N,N-dimethylformamide solvent, stir evenly, and then add 0.01 g of p-toluenesulfonic acid catalyst, react at 85 °C for 6 h, and then distill under reduced pressure and wash to obtain intermediate 2;

[0027] (5) 7 g of intermediate 2 and 6 g of mercaptoethylamine were added to 85 ml of 1,4-dioxane solvent, stirred to dissolve, and then 0.1 g of triethylamine catalyst was added thereto, and the mixture was reacted at 55 °C for 8 h. After the reaction, the mixture was filtered and washed to obtain modified maleimide;

[0028] (6) Add 1 g of polyethylene glycol, 0.8 g of sodium carboxymethyl cellulose, 5 g of acrylate, 6 g of glycidyl methacrylate, 4 g of silicone rubber-modified cellulose, 7 g of modified maleimide, and 10 g of deionized water into a stirrer and stir at 25 °C for 5 min to obtain a high adhesion coating.

[0029] Example 2

[0030] (1) Add 0.02 g of inhibitor dibutyl hydroxytoluene, 0.03 g of catalyst chloroplatinic acid, and 1 g of acrylamide to 85 ml of N,N-dimethylformamide solvent, stir evenly, then add 1.2 g of silicone rubber, disperse evenly by ultrasonication, react at 80 ° C for 14 h, cool after reaction, centrifuge, wash and dry to obtain amino silicone rubber;

[0031] (2) 2 g of maleic anhydride and pimaric acid was added to the reactor, heated in an oil bath at 120°C for 22 min, and then 3.2 g of amino silicone rubber was added under stirring. After the addition, the reaction was continued for 6 h. After the reaction was completed, the reaction was cooled to room temperature and washed to obtain intermediate 1.

[0032] (3) Add 10 g of cellulose to a 4% sodium hydroxide aqueous solution, then dropwise add 14 g of epichlorohydrin and 100 ml of ethanol solvent, stir and react at 80°C for 6 h to obtain epoxy cellulose, then add 13 g of intermediate 1 and 0.3 g of triethylamine catalyst to carry out a ring-opening reaction, react at 95°C for 10 h, filter and wash after the reaction to obtain silicone rubber modified cellulose;

[0033] (4) Add 1 g of 4-maleimidophenol and 1.2 g of intermediate 1 to 90 ml of N,N-dimethylformamide solvent, stir evenly, and then add 0.03 g of p-toluenesulfonic acid catalyst, react at 110 °C for 10 h, and then perform vacuum distillation and wash to obtain intermediate 2;

[0034] (5) 10 g of intermediate 2 and 15 g of mercaptoethylamine were added to 110 ml of 1,4-dioxane solvent, stirred to dissolve, and then 0.4 g of triethylamine catalyst was added thereto, and the mixture was reacted at 70 °C for 12 h. After the reaction, the mixture was filtered and washed to obtain modified maleimide;

[0035] (6) Add 2 g of polyethylene glycol, 1.1 g of sodium carboxymethyl cellulose, 8 g of acrylate, 9 g of glycidyl methacrylate, 8 g of silicone rubber-modified cellulose, 10 g of modified maleimide, and 15 g of deionized water into a stirrer and stir at 30 °C for 10 min to obtain a high adhesion coating.

[0036] Example 3

[0037] (1) Add 0.015 g of inhibitor dibutyl hydroxytoluene, 0.02 g of catalyst chloroplatinic acid, and 1 g of acrylamide to 75 ml of N,N-dimethylformamide solvent, stir evenly, then add 1.1 g of silicone rubber, disperse evenly by ultrasonication, react at 75 °C for 10 h, cool after reaction, centrifuge, wash and dry to obtain amino silicone rubber;

[0038] (2) 1.5 g of maleic anhydride pimaric acid was added to the reactor, heated in an oil bath at 115°C for 20 min, and then 2.8 g of amino silicone rubber was added under stirring. After the addition, the reaction was continued for 4 h. After the reaction was completed, the reaction was cooled to room temperature and washed to obtain intermediate 1.

[0039] (3) 8 g of cellulose was added to a 3% sodium hydroxide aqueous solution, and then 10 g of epichlorohydrin and 85 ml of ethanol solvent were added dropwise, and the mixture was stirred at 72°C for 5 h to obtain epoxy cellulose. 11 g of intermediate 1 and 0.2 g of triethylamine catalyst were added thereto to carry out a ring-opening reaction, and the mixture was reacted at 85°C for 8 h. After the reaction, the mixture was filtered and washed to obtain silicone rubber-modified cellulose.

[0040] (4) Add 1 g of 4-maleimidophenol and 1.15 g of intermediate 1 to 80 ml of N,N-dimethylformamide solvent, stir evenly, and then add 0.02 g of p-toluenesulfonic acid catalyst, react at 95 °C for 8 h, and then distill under reduced pressure and wash to obtain intermediate 2;

[0041] (5) 9 g of intermediate 2 and 12 g of mercaptoethylamine were added to 90 ml of 1,4-dioxane solvent, stirred to dissolve, and then 0.3 g of triethylamine catalyst was added thereto, and the mixture was reacted at 62 °C for 10 h. After the reaction, the mixture was filtered and washed to obtain modified maleimide;

[0042] (6) 1.5 g of polyethylene glycol, 0.9 g of sodium carboxymethyl cellulose, 7 g of acrylate, 8 g of glycidyl methacrylate, 6 g of silicone rubber-modified cellulose, 9 g of modified maleimide, and 12 g of deionized water were added into a stirrer and stirred at 28 °C for 8 min. After stirring, a high adhesion coating was obtained.

[0043] Example 4

[0044] (1) Add 0.01 g of inhibitor dibutyl hydroxytoluene, 0.02 g of catalyst chloroplatinic acid, and 1 g of acrylamide to 60 ml of N,N-dimethylformamide solvent, stir evenly, then add 1.1 g of silicone rubber, disperse evenly by ultrasonication, react at 65 ° C for 6 h, cool after reaction, centrifuge, wash and dry to obtain amino silicone rubber;

[0045] (2) 1 g of maleic anhydride pimaric acid was added to the reactor, heated in an oil bath at 110°C for 18 min, and then 1.1 g of amino silicone rubber was added under stirring. After the addition, the reaction was continued for 3 h. After the reaction was completed, the reaction was cooled to room temperature and washed to obtain intermediate 1.

[0046] (3) Add 10 g of cellulose to a 4% sodium hydroxide aqueous solution, then dropwise add 14 g of epichlorohydrin and 100 ml of ethanol solvent, stir and react at 80°C for 6 h to obtain epoxy cellulose, then add 13 g of intermediate 1 and 0.3 g of triethylamine catalyst to carry out a ring-opening reaction, react at 95°C for 10 h, filter and wash after the reaction to obtain silicone rubber modified cellulose;

[0047] (4) Add 1 g of 4-maleimidophenol and 1.2 g of intermediate 1 to 90 ml of N,N-dimethylformamide solvent, stir evenly, and then add 0.03 g of p-toluenesulfonic acid catalyst, react at 110 °C for 10 h, and then perform vacuum distillation and wash to obtain intermediate 2;

[0048] (5) 9 g of intermediate 2 and 12 g of mercaptoethylamine were added to 90 ml of 1,4-dioxane solvent, stirred to dissolve, and then 0.3 g of triethylamine catalyst was added thereto, and the mixture was reacted at 62 °C for 10 h. After the reaction, the mixture was filtered and washed to obtain modified maleimide;

[0049] (6) 1.5 g of polyethylene glycol, 0.9 g of sodium carboxymethyl cellulose, 7 g of acrylate, 8 g of glycidyl methacrylate, 6 g of silicone rubber-modified cellulose, 9 g of modified maleimide, and 12 g of deionized water were added into a stirrer and stirred at 28 °C for 8 min. After stirring, a high adhesion coating was obtained.

[0050] Example 5

[0051] (1) Add 0.02 g of inhibitor dibutyl hydroxytoluene, 0.03 g of catalyst chloroplatinic acid, and 1 g of acrylamide to 85 ml of N,N-dimethylformamide solvent, stir evenly, then add 1.2 g of silicone rubber, disperse evenly by ultrasonication, react at 80 ° C for 14 h, cool after reaction, centrifuge, wash and dry to obtain amino silicone rubber;

[0052] (2) 2 g of maleic anhydride and pimaric acid was added to the reactor, heated in an oil bath at 120°C for 22 min, and then 3.2 g of amino silicone rubber was added under stirring. After the addition, the reaction was continued for 6 h. After the reaction was completed, the reaction was cooled to room temperature and washed to obtain intermediate 1.

[0053] (3) 8 g of cellulose was added to a 3% sodium hydroxide aqueous solution, and then 10 g of epichlorohydrin and 85 ml of ethanol solvent were added dropwise, and the mixture was stirred at 72°C for 5 h to obtain epoxy cellulose. 11 g of intermediate 1 and 0.2 g of triethylamine catalyst were added thereto to carry out a ring-opening reaction, and the mixture was reacted at 85°C for 8 h. After the reaction, the mixture was filtered and washed to obtain silicone rubber-modified cellulose.

[0054] (4) Add 1 g of 4-maleimidophenol and 1.15 g of intermediate 1 to 80 ml of N,N-dimethylformamide solvent, stir evenly, and then add 0.02 g of p-toluenesulfonic acid catalyst, react at 95 °C for 8 h, and then distill under reduced pressure and wash to obtain intermediate 2;

[0055] (5) 7 g of intermediate 2 and 6 g of mercaptoethylamine were added to 85 ml of 1,4-dioxane solvent, stirred to dissolve, and then 0.1 g of triethylamine catalyst was added thereto, and the mixture was reacted at 55 °C for 8 h. After the reaction, the mixture was filtered and washed to obtain modified maleimide;

[0056] (6) Add 1 g of polyethylene glycol, 0.8 g of sodium carboxymethyl cellulose, 5 g of acrylate, 6 g of glycidyl methacrylate, 4 g of silicone rubber-modified cellulose, 7 g of modified maleimide, and 10 g of deionized water into a stirrer and stir at 25 °C for 5 min to obtain a high adhesion coating.

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 5 is that cellulose is used instead of silicone rubber to modify cellulose.

[0059] Comparative Example 2

[0060] The difference between this comparative example and Example 5 is that maleimide is used instead of modified maleimide.

[0061] Comparative Example 3

[0062] The difference between this comparative example and Example 5 is that cellulose is used instead of silicone rubber to modify cellulose, and maleimide is used instead of modified maleimide.

[0063] The high adhesion coatings obtained in Examples 1-5 and Comparative Examples 1-3 were uniformly coated on the surface of the diaphragm, dried at 60°C, double-sided coated, and the single-sided coating thickness was 2 microns (μm). The thickness of the diaphragm was 9μm. The diaphragm was Enjie diaphragm HS9, and a high adhesion composite film was obtained. The high adhesion composite film was soaked in water at room temperature for 15 minutes, and then the composite diaphragm was dried at 70°C to obtain a ceramic diaphragm for lithium-ion batteries.

[0064] Glass transition temperature: Differential scanning calorimetry (DSC) was used, with a scanning range of -60°C-100°C and a speed of 20°C / min. The peeling force between the diaphragm and the high adhesion coating was tested in the following manner: Sampling method: Cut a rectangular sample with a width of 20 mm and a length of 200 mm. Test method: The coated surface of the sample was attached to a steel plate with double-sided tape, and the other end of the sample was attached to another steel plate with double-sided tape in the opposite direction. The two steel plates were parallel and fixed on the upper and lower mold clamps, and then a universal tensile tester (HNB-200NPC) was used with a speed of 50 mm per minute, an angle of 180°, a tensile force of 50 N, and a displacement of 50-60 mm to complete the test.

[0065] Table 1: Performance tests.

[0066]

[0067] It can be seen from Table 1 that Examples 1-5 of the present invention have better viscosity, heat resistance and high temperature resistance than Comparative Examples 1-3.

[0068] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high adhesion coating, characterized in that: The invention comprises the following components by weight: 1-2 parts by weight of polyethylene glycol, 0.8-1.1 parts by weight of sodium carboxymethyl cellulose, 5-8 parts by weight of acrylate, 6-9 parts by weight of glycidyl methacrylate, 4-8 parts by weight of silicone rubber modified cellulose, 7-10 parts by weight of modified maleimide, and 10-15 parts by weight of deionized water; The preparation method of the silicone rubber modified cellulose is as follows: (1) Adding the polymerization inhibitor butylated hydroxytoluene, the catalyst chloroplatinic acid and acrylamide to N,N-dimethylformamide solvent, stirring evenly, then adding silicone rubber, ultrasonically dispersing evenly, reacting at 65-80°C for 6-14h, cooling after reaction, centrifuging, washing and drying to obtain amino silicone rubber; (2) Add maleic anhydride and pimaric acid into the reactor, heat in an oil bath at 110-120°C for 18-22 minutes, then add amino silicone rubber under stirring, continue to react for 3-6 hours after addition, cool to room temperature after completion, wash, and obtain intermediate 1; (3) adding 5-10 parts by weight of cellulose to a sodium hydroxide aqueous solution, then dropwise adding 9-14 parts by weight of epichlorohydrin and ethanol solvent, stirring and reacting at 65-80° C. for 3-6 hours to obtain epoxy cellulose, further adding 8-13 parts by weight of intermediate 1 and 0.1-0.3 parts by weight of triethylamine catalyst to the mixture, carrying out a ring-opening reaction, reacting at 70-95° C. for 6-10 hours, filtering and washing after the reaction, and obtaining silicone rubber-modified cellulose; The mass ratio of the polymerization inhibitor butylated hydroxytoluene, the catalyst chloroplatinic acid, acrylamide and silicone rubber in (1) is 0.01-0.02:0.02-0.03:1:1.1-1.2; The mass ratio of maleic anhydride pimaric acid to amino silicone rubber in (2) is 1:1.1-1.6; The mass fraction of the sodium hydroxide aqueous solution in (3) is 2-4%; The modified maleimide is: S1. Add 4-maleimidophenol and intermediate 1 to N,N-dimethylformamide solvent, stir evenly, continue to add p-toluenesulfonic acid catalyst, react at 85-110°C for 6-10h, and then distill under reduced pressure and wash to obtain intermediate 2; S2. 7-10 parts by weight of intermediate 2 and 6-15 parts by weight of mercaptoethylamine are added to 1,4-dioxane solvent, stirred to dissolve, and then 0.1-0.4 parts by weight of triethylamine catalyst is added thereto, reacted at 55-70° C. for 8-12 hours, filtered after completion, washed, to obtain modified maleimide; The mass ratio of 4-maleimidophenol, intermediate 1 and p-toluenesulfonic acid catalyst in S1 is 1:1.1-1.2:0.01-0.

03.

2. A method for preparing a high adhesion coating as claimed in claim 1, characterized in that: The preparation method of the high-adhesion coating is as follows: polyethylene glycol, sodium carboxymethyl cellulose, acrylate, glycidyl methacrylate, silicone rubber-modified cellulose, modified maleimide, and deionized water are added into a stirrer, and stirred at 25-30° C. for 5-10 minutes, and then the high-adhesion coating is obtained.

Citation Information

Patent Citations

  • Lithium battery modified coating diaphragm and preparation method thereof

    CN112909426A

  • TWO-COMPONENT THERMOHOLAR-RUBBER ITEM.

    BE1019810A3

  • Method of separating two adhered plates

    CN103214975A